The Importance of Chronotope in Literature - Yusufovna, Kakharova Mohigul (Indonesian Journal Publisher, 2025)
This study explores the significance of chronotope in literature, focusing on its role in shaping the unity of time and space in narrative structures. The research aims to analyze how chronotope functions in literary texts, comparing the works of American author Jack London and Uzbek writer Abdulla Qahhor to demonstrate how different lexical units convey hidden meanings and influence reader perception. The study employs a literary analysis methodology, incorporating conceptual analysis, interpretation of literary texts, and comparative analysis of genre and style. It examines lexical choices, narrative structures, and symbolic representations to understand how authors construct chronotope to enhance storytelling and ideological impact. The findings indicate that chronotope plays a crucial role in literary composition by structuring the plot, guiding character actions, and shaping thematic development. In Jack London's